1994
DOI: 10.1007/bf00802049
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability, sensitivity and content validity of the VECS and VSSS in measuring expectations and satisfaction in psychiatric patients and their relatives

Abstract: The Verona Expectations for Care Scale (VECS) and the Verona Service Satisfaction Scale (VSSS) are two newly developed, multidimensional instruments that measure expectations and satisfaction with community-based psychiatric services (CPS) in patients, relatives and professionals. This paper reports on the acceptability, sensitivity and content validity of the VECS and VSSS in 75 patients and 76 relatives attending the South-Verona CPS. The acceptability of the VECS and the VSSS to subjects was good: most item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 25 publications
0
48
0
3
Order By: Relevance
“…Satisfaction with mental health services was assessed using the Verona Service Satisfaction Scale (VSSSR; Ruggeri and Dall'Agnola, 1993; Ruggeri et al, 1994, 1996, 2007) which is designed for self-administration and can be completed without prior training in 20–30 min. The VSSS has been implemented both in the version for Patients and for Relatives (Ruggeri et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Satisfaction with mental health services was assessed using the Verona Service Satisfaction Scale (VSSSR; Ruggeri and Dall'Agnola, 1993; Ruggeri et al, 1994, 1996, 2007) which is designed for self-administration and can be completed without prior training in 20–30 min. The VSSS has been implemented both in the version for Patients and for Relatives (Ruggeri et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The Verona Service Satisfaction Scale [VSSS-54;Ruggeri et al, 1994], was used to measure satisfaction with mental health services; the items are rated on a sevenpoint Likert scale with global score reflecting higher satisfaction.…”
Section: Satisfaction Toward Care Servicesmentioning
confidence: 99%
“…Two factors seem particularly worthy of investigation in multi-factorial models: the first is satisfaction with care received (Ruggeri et al, 1994), a multidimensional concept which has been found to be associated with a higher number of unmet needs for care and lower QOL (Ruggeri et al, 2003). The second factor is represented by spiritual and religious well-being: in a recent study the QOL spiritual domain of patients with residual schizophrenia explained more than 64% of the variance of overall QOL score (Shah et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The previous literature concerning the effects of patient socio-demographic characteristics on service satisfaction remains inconclusive. On the one hand, no clear relationship has been found between satisfaction and psychosocial factors, such as marital status, occupation and education [39]; on the other hand, previous findings indicate that socio-demographic variables have only a modest impact in the various domains of satisfaction [19,34,38,40,41]. In line with these findings in the present study, we found that OCD patients without partner or spouse were more dissatisfied in the type of interventions, similar to the patients without positive family history.…”
Section: Discussionmentioning
confidence: 99%